Xây dựng và sử dụng từ điển điện tử Anh - Việt các thuật ngữ chuyên ngành báo chí - truyền thông nhằm nâng cao hiệu quả dạy và học: Nghiên cứu tại Trường Đại học Khánh Hòa - Thái, Nguyên Hoàng Giang; Đào, Mộng Uyển (Tạp chí Giáo dục, 2025)
Digital transformation in education requires the active application of technology in teaching to meet current demands. The English-Vietnamese electronic dictionary of Journalism and Communication terminology is a valuable tool to improve the quality of teaching and learning in this field. This article provides an overview of the digitization of the English-Vietnamese dictionary of Journalism and Communication terminology and its application in teaching this subject. From there, it suggests several solutions to enhance the effectiveness of its use as well as directions for improving the dictionary in teaching to align with the digital transformation trend at Khanh Hoa University. Effectively utilizing the electronic dictionary not only enhances students’ specialized English proficiency but also promotes teaching and learning practices that align with the modern digital education environment.